1989
DOI: 10.1093/carcin/10.8.1475
|View full text |Cite
|
Sign up to set email alerts
|

Comparative tumorigenicity of N-nitroso-2-hydroxymorpholine, N-nitrosodiethanolamine and N-nitrosomorpholine in A/J mice and F344 rats

Abstract: N-Nitroso-2-hydroxymorpholine (NHMOR), a genotoxic metabolite of the environmental carcinogens N-nitrosomorpholine (NMOR) and N-nitrosodiethanolamine (NDELA), was assayed for tumorigenicity in A/J mice and F344 rats. Groups of female mice were given NHMOR, NMOR or NDELA in the drinking water over a 10-week period; total doses were 53-55 mumol/mouse. The experiment was terminated after 30 weeks. Whereas NMOR was a potent tumorigen, inducing 20.3 lung tumors/mouse, NHMOR and NDELA were only weakly tumorigenic, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…The latter paths are expected to lead to carcinogenesis. Such a phenomenon, that is, further oxidation of NHMOR at carbons 3 or 5 before it escapes from the P450 active site, could explain why Hecht et al failed to observe carcinogenic activity for orally administered NHMOR (77). It is possible that most of this material is detoxified by cytosolic enzymes before it reaches the endoplasmic reticulum where high concentrations of P450 are located.…”
Section: Methodsmentioning
confidence: 99%
“…The latter paths are expected to lead to carcinogenesis. Such a phenomenon, that is, further oxidation of NHMOR at carbons 3 or 5 before it escapes from the P450 active site, could explain why Hecht et al failed to observe carcinogenic activity for orally administered NHMOR (77). It is possible that most of this material is detoxified by cytosolic enzymes before it reaches the endoplasmic reticulum where high concentrations of P450 are located.…”
Section: Methodsmentioning
confidence: 99%
“…The most significant challenge to the β-oxidation pathway comes from carcinogenesis experiments utilizing NHMOR. Lijinsky and Hecht found that NHMOR is not carcinogenic in F344 rats and only weakly carcinogenic in A/J mice (44). While it can be argued that administration of NHMOR in the drinking water does not result in its arrival at the proper compartment in the liver to elicit its carcinogenic action, its lack of carcinogenicity, and additional confounding factors presented above, raise doubts regarding the β-oxidation hypothesis and the mode of NDELA carcinogenic activation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, via the oral route the main target organ of NMPA and NMBA is the esophagus in rats (Lijinsky et al, 1983) while it is the liver in the hamster . Furthermore, the main target organ of NDELA via the oral route in the rat is the liver, while in the mouse it is the lung (Hecht et al, 1989).…”
Section: Target-organs Of Tumor Formationmentioning
confidence: 99%